(untitled) (Conferencea, 2022)
Enter.Metal drawing process. In the manufacturing industry, the metal drawing process is usually carried out cold. Cold working gives the drawn product precise tolerances, favorable grain structure, improved material properties and good surface finish. Preparation of the work before drawing is an important part of the operation. The work is sometimes annealed first to recover the material from existing stresses. Afterwards, the workplaces are cleaned. A common industrial practice for cleaning metal stock involves blasting or immersion in some (usually acidic) solution. The work can then be washed to remove any solution, and can also be dried at low temperature. After the cleaning step, the stock may be conditioned, which may involve the application of various chemical solutions to the work surface. The specific chemicals used depend on the manufacturing situation and the work material. The main purpose of these conditioning agents is to help the work surface retain the oil required for the process[1-2].